An In-Depth Exploration of Elementary Teachers' Views on Assessing Learning Within the Independent Curriculum - Friska Ria Sitorus; Nova Mawar Hutabarat; Perida Roma Asi Siahaan (Bahasa Indonesia Prima, 2025)
Education plays a vital role in the entire learning journey, every teaching and learning activity is directed toward fulfilling the goals established in the educational program. The merdeka curriculum emphasizes individualized assessments to address the diverse needs of students. however, its effectiveness in fully accommodating the varying characteristics of each student remains uncertain. Underlining the importance of ongoing assessment and refinement. this qualitative descriptive study integrates a literature review and in-depth interviews to examine the implementation of the independent curriculum from the perspectives of elementary school teachers. five participants were purposively selected—experienced teachers from public and private elementary schools in north sumatra—based on their enrollment in a learning evaluation course during their master’s program. through in-depth interviews, the study captures their reflections, experiences, and challenges in applying the curriculum in classroom settings. this study found that learning evaluation is an indispensable element of effective education. it is not only used to assess student achievement but also to improve the quality of the teaching process. since each evaluation method has its own advantages and limitations, teachers must wisely combine and balance different strategies to create a more inclusive, fair, and continuous learning experience for all students.